Strategi Pembelajaran Berdiferensi: Akselerasi Meningkatkan Potensi Peserta Didik - Rusmala Siringoringo; Masduki Asbari; Cesilia Margaretta (AGUSPATI RESEARCH INSTITUTA, 2023)
Abstract - The Merdeka Curriculum is synonymous with learning that supports students, as well as differentiated learning. Differentiated learning is really needed by students to carry out a learning approach that allows teachers to meet the individual needs of each student in the class. The aim of this research is to provide learning experiences that are relevant, challenging, and appropriate to the individual's level of understanding and learning style.In this study report, a qualitative descriptive method was used by listening because the data source was obtained by listening to oral narratives from the YouTube channel Young Teacher Notes entitled